Clinical and microbiological evaluation of dental plaque on topical application of olive oil, olive oil with 35% Curcuma zedoaria, and olive oil with 30% Azadirachta indica in hospitalized children: A randomized control trial - Anshula Deshpande; Simron Baishya; Sneha Dori; Medha Wadhwa; Khushali Shah (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2025)
Background: Hospitalized children find difficulty in performing regular oral hygiene procedures. In such cases, direct application of herbal oils such as olive oil, Azadirachta indica (AI) (neem), and Curcuma zedoaria (CZ) (white turmeric) as antiplaque agents could be beneficial in maintaining oral hygiene. Aim: The aim of the study was to evaluate the efficacy of normal saline, extra virgin olive oil (EVOO), EVOO with 35% CZ, and EVOO with 30% AI on dental plaque and the count of Streptococcus mutans, Lactobacillus, and Candida albicans in hospitalized children. Settings and Design: This was a randomized control trial. Materials and Methods: 84 hospitalized children of age group 3–14 years were randomly divided by computer-generated random allocation into Group A-EVOO, Group B-EVOO + 35% CZ, Group C-EVOO + 30% AI, and Group D-normal saline with 21 participants in each group and applied with sterile gauze. The plaque score was recorded and analyzed by Loe and Silness plaque index. In addition, plaque sample for microbial analysis was collected from buccal/lingual surfaces, and CFU count was measured at baseline, 24 h, 48 h, and 72 h. Results: The four groups showed a reduction in plaque score and CFU counts from baseline to 72 h with P < 0.05 indicating a statistically significant difference. Group C has shown significant antimicrobial activity against Group A, Group B, and Group D (P = 0.0001) at 72 h. Conclusion: EVOO + 35% CZ showed the best treatment outcome in the reduction of microbial count followed by EVOO + 30% AI and EVOO. All the preparations including normal saline have antiplaque properties with the best outcome achieved in EVOO + 35% CZ and EVOO + 30% AI preparations.